"A shift in the playing field": Indigenous sovereignty and the philosophy of Jacques Ranciѐre. (March 2017) - Ruckstuhl, Katharina
This article considers Indigenous people as political actors in their quest for sovereignty within the liberal democracies of Canada, Australia, Aotearoa New Zealand and the USA (the CANZUS nations). I aim to show that, despite the structures of settler colonialism that both resist and then co-opt dissent, seeking sovereignty is, as political philosopher Jacques Ranciѐre outlines, an act of Indigenous politics that challenges and shifts these structures. While the fundamental colonising logic of the nation state does not change, through the Indigenous sovereign voice, a reframed understanding of democracy is revealed which in turn creates an enlarged space for Indigenous peoples.